PERAN SANGGAR Al-BAROKAH DALAM KEBERADAAN KESENIAN RANDAIDI KORONG RIMBO PANJANG KABUPATEN PADANG PARIAMAN - Vina Kusuma Wardani; Hakim, Uswatul (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to determine the creativity process, inhibiting factors and interests of teenagers at the Al-Barokah Mosque in the existence of randai art in Korong Rimbo Panjang, Padang Pariaman Regency. This type of research is qualitative research with a descriptive approach. Informants in this study focused on the founder of the Al-Barokah studio. The research instrument was the researcher himself and assisted by stationery and a camera. Data were collected through literature studies, observations, interviews and documentation. The steps for analyzing data are data collection, reduction, presentation and conclusion. The results of the study indicate that the interest/performers of teenagers still looks strong because randai members want to be better known to the public through their performances. Randai members think that randai art has values ​​that can shape the character of society better than modern entertainment. The creative process at Al-Barokah begins with the recruitment of Randai members from among Islamic boarding school students (santri-wati) and the surrounding community, followed by training through the stages of script material and movements, up to dress rehearsal. Training is conducted using a discussion approach, for both old and new members, held once a week. Performances focus on increasing the intensity of practice to strengthen the confidence of members, especially beginners, by performing in open spaces, flats, and indoors. Factors inhibiting the role of the Al-Barokah studio include low member motivation due to the lack of awards and incentives for Randai members, limited facilities and infrastructure, foreign culture, and increasingly modern technological developments.